2020
DOI: 10.3390/ijerph17176364
|View full text |Cite
|
Sign up to set email alerts
|

How Spiritual Leadership Boosts Nurses’ Work Engagement: The Mediating Roles of Calling and Psychological Capital

Abstract: Work engagement is an important topic in the field of nursing management. Meanwhile, spiritual leadership has been demonstrated to have a positive impact on healthcare workers. However, the relationship between spiritual leadership and work engagement is unclear. The main purpose of this study was to investigate the influence of spiritual leadership on work engagement through increased spiritual well-being and psychological capital. This study used a cross-sectional survey to collect data in Taiwan. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 48 publications
2
37
0
10
Order By: Relevance
“…The results obtained from PLS SEM generally supported the hypothesised relationships. The results provided strong support for the influence of EI on work locus of control (Ng et al, 2014;Singh, 2006), EI on psychological capital (Gong et al, 2019), work locus of control on psychological capital (Shaik & Buitendach, 2015), calling orientation on psychological capital (Wu & Lee, 2020), psychological capital on employee engagement (Allesandri et al, 2018;Simons & Buitendach, 2013) and calling orientation on employee engagement (Ugwu & Nyishi, 2017;Xie et al, 2016).…”
Section: Outline Of the Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The results obtained from PLS SEM generally supported the hypothesised relationships. The results provided strong support for the influence of EI on work locus of control (Ng et al, 2014;Singh, 2006), EI on psychological capital (Gong et al, 2019), work locus of control on psychological capital (Shaik & Buitendach, 2015), calling orientation on psychological capital (Wu & Lee, 2020), psychological capital on employee engagement (Allesandri et al, 2018;Simons & Buitendach, 2013) and calling orientation on employee engagement (Ugwu & Nyishi, 2017;Xie et al, 2016).…”
Section: Outline Of the Resultsmentioning
confidence: 91%
“…A cross-sectional study conducted by Hirschi (2012) amongst 259 heterogeneous employees in Germany demonstrated that a positive association exists between calling orientation and occupational self-efficacy (a dimension of psychological capital). A study by Wu and Lee (2020), however, provided more specific evidence of the strong relationship between calling and psychological capital (b = 0.43, p < 0.0001) in a sample of 164 Taiwanese nurses. The researchers, therefore, formulated the following hypothesis:…”
Section: Work Locus Of Controlmentioning
confidence: 96%
“…Many studies have recognized that it is important to have employees who are engaged in their work. Thus, work engagement, defined as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption, has become an important issue in the past few years [18][19][20]. Studies on the influencing factors of work engagement, in addition to personal factors, the most discussed included job resources, perceived supports, learning organizations, and transformational leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative methods are, by far, the prevalent choice used to investigate this connection (Vasconcelos, 2018). The findings from quantitative studies (Afsar & Rehman, 2015;Albuquerque et al, 2014;Garg, 2017;Kolodinsky et al, 2008;Petchsawang & Duchon, 2012;Phuong et al, 2018;Rego & Pina e Cunha, 2008;Wu & Lee, 2020) are remarkably consistent in that they show, albeit to varying extents, a statistically significant positive correlation between spiritual well-being and work performance. This consistency displayed in extant research is notable.…”
Section: Spiritual Well-being and Work Performance -Evidence And Gapsmentioning
confidence: 86%
“…The connection between spiritual well-being and work performance has been widely studied empirically across different business disciplines, including leadership (Wu & Lee, 2020), human resource management (Joelle & Coelho, 2019), hospitality and tourism (Milliman et al, 2018), psychology (Moon et al, 2020) and management (Fox et al, 2018;Singh & Chopra, 2018). In the past two decades, empirical studies have also been conducted in different countries, such as in The United States of America (Tejeda, 2015), Portugal (Albuquerque et al, 2014), Canada (Kinjerski & Skrypnek, 2008), India (Sengupta, 2010); China (Wang et al, 2019), South Korea (Kim & Yeom, 2018), Taiwan (Chen & Yang, 2012), Thailand (Petchsawang & Duchon, 2012), Malaysia (Wan Yunan et al, 2018), and Pakistan (Hassan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%